Kolaborasi KUA Dengan Masyarakat Multikultural: Mewujudkan Medan Tembung Yang Damai - Wirman; Abdi Saad Zuharum; Aulia Siddiq Siregar; Diki Darmawan; Fauzy Rahman; Fani Nurmalina; Siti Nurliana Siregar (STIT Syekh Muhammad Nafis Tabalong, 2026)
This study aims to analyze collaboration between the Office of Religious Affairs (KUA) and the multicultural community to realize a peaceful Medan Tembung District. The research focuses on the form of collaboration among the KUA, religious leaders, community leaders, and social institutions; the KUA's strategic role in fostering religious life amid diversity; and the effectiveness of programs in building tolerance and preventing social conflict. This study uses a qualitative, descriptive approach. Data collection techniques included observation, in-depth interviews, and documentation, with data analysis using an interactive model. The results indicate that the KUA's collaboration with various community elements is well-functioning and participatory. The KUA acts as an effective facilitator and mediator in maintaining social harmony. The implemented programs have proven effective in increasing tolerance awareness and reducing the potential for conflict, although obstacles such as limited resources and differences in community understanding persist. Overall, the KUA's collaboration has made a significant contribution to creating a harmonious and peaceful society amidst diversity.